The Relationship between Decision Support Systems and Organizational Effectiveness: Case Study of Arab Potash Company - Aboalganam, Khaled (The Arab Journal of Administration, 2018)
This study aimed at knowing the nature of the relationship between decision support systems and organizational effectiveness in the Arab Potash Company. A questionnaire of sixty -three items was designed and administered among 435. Only 301 forms were received, and the data was processed by the use of SPSS V-16. The results revealed that there was a positive relationship (a = 0.05 or less) between all the decision support systems and organizational effectiveness. Furthermore, the results showed a statistical significance difference at the level (a = 0.01 or less) in the personnel’s perception toward organizational effectiveness due to age, qualifications and work level variables. The study recommended directing the Company managers to review and develop the technological elements of decision support systems, adopting latest developments, as decision support systems is an essential element in administrative efficiency, and urge mangers to conduct extensive training to their employees to exploit the capabilities of decision support systems. It also recommended conducting further studies on the promotion of collective decision systems and its relationship with the participation of administrative knowledge and administrative efficiency.